From field to suburb: investigating a planted monastic settlement at Barnwell, Cambridge. Issue 1 (2nd January 2021) - Newman, Richard
ABSTRACT: At the beginning of the thirteenth century a planted development was established outside the gates of the Augustinian Priory at Barnwell, Cambridge. Although dislocated from the urban core by a kilometre of open fields, the new settlement nevertheless expanded rapidly; by the close of the thirteenth century, it housed almost one-sixth of the town's overall population and had attained the legal status of a suburb. Utilising a combination of archaeological evidence and historical sources, the settlement's origins, development and wider context are explored. In particular, its 'suburban' character is examined via a comparison of patterns of refuse disposal undertaken at a variety of sites situated elsewhere across Cambridge and its hinterland. Despite its early success, during the fifteenth century Barnwell's population began to decline. The settlement's diminution continued into the post-medieval period, until the area was eventually transformed via intensive speculative development into Cambridge's largest nineteenth-century suburb.